Prawodawca i jego sztuka - Kroczek, Piotr (Prawo Kanoniczne, 2007)
This article originated in an effort to present a church lawgiver, his work, and some of the rules the lawgiver’s work needs to follow to become an art. Rules for making the law should not stand in isolation from the rules that govern the interpretation of that law. In fact, rules for making the law should follow the rules of interpreting that very law. The article consists of two parts. The first one presents the theory of lawgiving while the second offers the rules in question. These rules can be grouped into three categories. Rules in terms of the person of the lawgiver: 1. Get to know yourself, 2. Be aware of your philosophical and theological horizon, 3. Be prudent, 4. Acquire proper knowledge, 5. Thoroughly estimate the results of the chosen law solution and its alternatives. Rules in term s of the community: 1. Take under consideration a community you serve, 2. Predict an acceptance of law, 3. Take care of acceptance and reception of law, 4. Listen to voices of community after the law comes into force. Rules in term s of the text of the law: 1. Remember the role of the law in the Church, 2. Take care of the theological correctness of the law, 3. Make the law according to the thought of the Second Vatican Council, 4. Be familiar with the existing legislative system, 5. Do your best to formulate a clear law, 6. Take into account the common law, 7. Create a form of the law adequate to its importance, 8. Use proper language to write the law (take care of correct translation), use proper words, and remember about the context of used words, 9. Be aware that your words will be interpreted in wide or narrow way. The lawgiving activity takes place within the church itself. It does not come to it from the outside. It flows naturally from the Church’s mission to teach. The exercise of authority in the Church, and that includes the legislature, has its roots in love. When it fails to rely on love it is no longer a Church authority. The process of making church law can be called after L. Orsy: a small participation in the great love of God that presently and perpetually creates the Christian community. We see that acting in accordance with love a church legislator is capable of turning his work into art.